NUMERICAL EVALUATION OF THE CRACK- DRIVING FORCE IN HETEROGENEOUS REGIONS - Praunseis, Zdravko (Journal of Energy Technology, 2024)
An attempt to evaluate numerically the crack-driving force CTOD - 5 for welded joints with a strength mismatch has been made with use of the finite element method. The crack-driving force, i.e. the parameter CTOD - 5, for specimens with shallow cracks in welded joints with homogeneous and heterogeneous welds, has been determined at the point of instability. Different yield strengths of different microstructures around the crack tip and its actual mechanical properties are taken into account in the finite element method model of bending specimens. The idea of the numerical evaluation of the CTOD - 5 parameter is to evaluate the crack-driving force and to compare it with the experimental value in order to estimate if brittle or ductile fractures will be initiated.